Symbiotic Relationship between a Healthy Population and a Sustainable Economy: Financial Performance of Julphar Gulf Pharmaceutical Industries - Olorogun, Lukman Ayinde; Yalciner, Kursat; Al Jaberi, Abdulla Sultan (International Journal of Economics and Financial Issues, 2020)
Redefining the variables of macroeconomics requires the evaluation of the vital role the healthcare industry plays as an economic agent. The pharmaceutical industry constitutes a vital part of the healthcare industry. In this study, the evaluation of the performance of Julphar examined viability of such an agent. A 5-year financial ratio analysis was conducted based on the company’s 5-year annual reports. The analyzed ratios were assets utilization, net profit margin, debt utilization, and the profitability ratios ROA and ROE. The overall findings showed that Julphar assets were underutilized meaning that their productivity is not optimal. ROA and ROE dropped-down consecutively, which means that the company’s profitability was in question given its high debt-financing and a continuous increase in total operating expenses. This performance can affect the national and regional economic stability. It is recommended that Julphar scales down financing, debt acquisitions, and reduces its operating expenses while increasing its productivity by way of optimal assets utilization and redefined market segmentation. Market-driven projects are seen as the solution to most of its problems. Due to its position, Julphar plays important role in the national and regional economy. Future research should include other microeconomic agents such as micro-foundations in order to determine the far-reaching effects of financial performance on the economy. Keywords: Financial Performance, Healthcare, Economy, Pharmaceutical Industry, Macroeconomics JEL Classifications: G32; G49; I15; O11 DOI: https://doi.org/10.32479/ijefi.9406